Quotation for escalator roof canopy works - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This variation order has been made between Brac University and BUCG-ABC joint venture for quotation for escalator roof canopy worksof Brac University new campus project.